Syndicaliste et administrateur de la SNCF - Marnix Dressen; Christian Mahieux (La Nouvelle Revue du Travail)
The article reflects both upon the location of core power within companies such as SNCF French National Railways and also on the various forms that “social democracy” might assume in such environments. The authors engage in a sociographic study of SNCF headquarter employees, asking what happens behind closed doors at board of directors meetings and how the balance of power lies in arguments between different categories of board members. A third analysis delves into specific case studies, with the authors focusing on interactions between employee board members and the parties they represent. The conclusion highlights how challenging it is for organisations claiming to engage in revolutionary unionism to make space for themselves in organisations that are under strict state control yet pursue more or less commercial ambitions.